Socio-stylistic aspects of linguistic variation: schooling and monitoring effects - Raquel Meister Ko. Freitag (Acta Scientiarum. Language and Culture, 2015)
Alveolar stops following palatal glide in Brazilian Portuguese are investigated, with focus on constraints for the choice between occlusive or affricate variants. Data was collected in the community of practice of Praesidium Mãe da Divina Graça da Legião de Maria, from a sample belonging to the ‘Falares Sergipanos’ database, and submitted to GoldVarbX analysis. Seven hundred seventy-five variable contexts were identified, in which 550 occurrences corresponded to the occlusive variant. Results show that the phenomenon is constrained by linguistic, social and stylistic factors, and highlight the importance of a detailed control of the context in the analysis of variable phenomena at the phonetic-phonological level.